A Body Shaping: Relationship between Life Satisfactions with Self-Esteem - Khan, Asma; Fizzah Rehman; Saima Shafiq (Dialogue Social Science Review (DSSR), 2024)
In our present time body shaping and body satisfaction are the biggest challenges of every individual’s life everyone should be possessive and conscious about body satisfaction. Diet and fitness in today's youth are the most common. That is true body satisfaction impacts individual life and their self-esteem. The present study investigates the body-shaping relationship between life satisfaction and self-esteem among individuals whose age criteria are 18 to 35. The sampling technique is random sampling using Google Forum. The individual body image-conscious users who participated in the study were 100 individuals (50 male & 50 female). The study tool is a structured questionnaire. Body shaping questionnaire (BSQ), Rosenberg self-esteem measure, and the life satisfaction scale. The collected data was analyzed through IBM SPSS Statistics Version 22 in terms of descriptive statistics and correlation coefficients regression, and a simple t-test was also used. Self-esteem and body sculpting are positively correlated. p= .293. There is no distinction between both genders; boys and girls are equally possessive of their body image. The relationship between self-esteem and life satisfaction was found insignificant in this present study.